(untitled) (Conferencea, 2022)
This article is dedicated to the study of the phonetic features of English words and their variants. Before covering this issue, it is worthwhile to think about the features of the English phonetic system. In addition, paying special attention to this issue, recalling some historical information related to it, allows us to clarify the issue.